Life Cycle Assessment Analysis Based on Material Selection in Sustainable Airport Buildings - UĞURAL, MEHMET NURETTİN; ÖZYILMAZ, MERVE RÜYA; Burgan, Halil Ibrahim (MDPI, 2024)
Sustainable airport buildings aim to minimize environmental impacts through energy efficiency, water conservation, and waste management. This is achieved by employing green building materials and utilizing renewable energy sources to reduce their carbon footprint. In this study, life cycle assessment (LCA) was conducted to assess the environmental impacts of three main construction materials—concrete, steel, and wood—used in sustainable airport buildings. These materials were selected for their widespread use in eight different airport terminal buildings with sustainability certifications. The environmental impacts of these materials were calculated and compared using OpenLCA 1.9.0 software and the ECOinvent database, adhering to the standards set forth by the Environmental Product Declaration (EPD) initiative. The findings indicate that wood, as a construction material, has a significantly lower impact on global warming compared to steel and concrete, with a global warming potential (GWP) ratio of less than 60%. Steel, with a GWP of approximately 90% of that of concrete, also showed a lower impact than concrete. Additionally, other environmental impacts, such as stratospheric ozone depletion potential (ODP) and acidification potential (AP), were also examined, highlighting the trade-offs associated with each material. © 2024 by the authors.
Keywords: Airport; Building Materials; Life Cycle Assessment (LCA); Project Management; Sustainability